Enabling perfusion through multicellular tumor spheroids promoting lumenization in a vascularized cancer model. Issue 22 (13th October 2022) - Park, Joonha; Kim, Seunggyu; Hong, Jiman; Jeon, Jessie S.
Abstract : Tumor microenvironment recapitulation focusing on perfusable multicellular tumor spheroid model construction via anastomosis of endothelial cells through the spheroid increases the overall growth and penetration of the anti-cancer drug. Abstract : A tumor is composed of heterogeneous cell population, which is known as tumor stroma. In particular, blood vessels have an indispensable role in the tumor microenvironment acting as a key player in anti-cancer drug delivery. Recently, efforts have been made to accurately recapitulate the microenvironment by employing distinct cell types, however, the proper formation of perfusable tumor tissue is challenging. Here, perfusable tumor tissue is engineered by implanting multicellular tumor spheroids inside the microfluidic devices. Blood perfusion, spheroid growth, and vascular dynamics were monitored according to the spheroid composition and the contribution of internal and external vascular cells to spheroid perfusion was analyzed. Most notably, the increased penetration depth of fluorescence conjugated anti-cancer drug was observed in tri-culture spheroids. The implementation of tumor microenvironment reconstruction developed in this study not only creates a perfusable tumor vascular model but can also be utilized as a novel drug screening platform with patient-derived samples.